Correlated electronic phases in twisted bilayer transition metal dichalcogenides - Wang, Lei; Shih, En-Min; Ghiotto, Augusto; Xian, Lede; Rhodes, Daniel A.; Tan, Cheng; Claassen, Martin; Kennes, Dante M.; Bai, Yusong; Kim, Bumho; Watanabe, Kenji; Taniguchi, Takashi; et al. (Nature materials, 2020)
In narrow electron bands in which the Coulomb interaction energy becomes comparable to the bandwidth, interactions can drive new quantum phases. Such flat bands in twisted graphene-based systems result in correlated insulator, superconducting and topological states. Here we report evidence of low-energy flat bands in twisted bilayer WSe 2 , with signatures of collective phases observed over twist angles that range from 4 to 5.1°. At half-band filling, a correlated insulator appeared that is tunable with both twist angle and displacement field. At a 5.1° twist, zero-resistance pockets were observed on doping away from half filling at temperatures below 3 K, which indicates a possible transition to a superconducting state. The observation of tunable collective phases in a simple band, which hosts only two holes per unit cell at full filling, establishes twisted bilayer transition metal dichalcogenides as an ideal platform to study correlated physics in two dimensions on a triangular lattice. Tunable correlated states are observed in twist bilayer WSe 2 over a range of twist angles, with signatures of superconductivity for a twist of 5.1°.